An action research on promotion of health ageing and risk reduction of chronic disease : a need assessment study among rural elderly Malays, care givers and health professionals - Adznam, S.Nur Asyura; Shahar, S.; Rahman, S.A.; Yusof, N.A.M.; Arshad, F.; Yassin, Z.; Salleh, M.; Samah, A.A.; Sakian, N.I.M. (2009)
Prior to the development of a healthy ageing and risk reduction of chronic diseases intervention package for older people in Malaysia, a need assessment study was conducted to identify nutritional knowledge status and information needs, as part of an action research process. Design: A cross sectional study was conducted among 267 elderly people, 54 care givers and 66 health professionals in two rural areas of Peninsular of Malaysia (i.e Sabak Bernam, Selangor and Kuala Pilah, Negeri Sembilan). Information on nutritional knowledge was obtained from an interview based questionnaire for older subjects and caregiver and through self administered questionnaire from the health professionals. Anthropometric and functional measurements were also conducted among elderly subjects. Results: It was found that the elderly subjects had poor nutritional knowledge with 43.8% of them classified as having unsatisfactory nutritional knowledge, followed by moderately satisfactory (33.7%), very unsatisfactory (15.7%) and good (6.7%). Talks, counselling sessions with health professionals and electronic media such as television and radio were the most preferred nutrition education sources among elderly subjects and their care givers. The majority of health professionals studied (98.5%) had good nutritional knowledge. Although most of them (93.6%) were involved in management of the elderly, only 45.5% incorporated nutritional information component in this activity. Most of the health professionals used the guidelines for management of elderly patients (63.6%). However, nutritional knowledge was very minimal in these guidelines. Multiple regression analysis indicated that ‘level education’, involvement in ‘social activities’, presence of ‘hearing problems’, the Instrumental Activities of Daily Living (IADL) score, having previous ‘nutritional information’ and ‘participation in healthy eating programme’ were the major predictors of nutritional knowledge score among elderly subjects. Conclusion: Based on the above findings it is thus, imperative that an appropriate nutritional intervention package and programme be developed so as to help improve nutritional knowledge and subsequently the nutritional status of the rural elderly Malays.